INNOVATIVE WORKSHOP OF MASTERY REMOTE DESKTOP AND TEAMVIEWER FOR STUDENTS OF DHARMA VOCATIONAL SCHOOL KARAWACI OF COMPUTER NETWORK DEPARTMENT - Taswanda Taryo; Achmad Hindasyah; Agung Budi Susanto; Farkhan Mubarok; Nining Suharwati; Dahlan Supriatna; Suharyadi; Gregorius Eduard D. P.; Entis Sutisna; Mukhlishoh Syaukati Robbi; Ajeng Permata Suri (Bajang Institute, 2025)
Information and communication technology (ICT) has become the backbone of various industrial sectors. There are many applications that can be offered to solve computer repair problems remotely and Remote Desktop and TeamViewer applications are two of them. Dharma Siswa Karawaci Vocational School is committed to preparing graduates who are ready to work and highly competitive in the industrial world. The PKM of Postgraduate Program in Informatics Engineering, Pamulang University-UNPAM conducted an innovative workshop on Remote Desktop and TeamViewer on October 19, 2024. A survey showed they are satisified to participate in the workshop. Student participants can improve the skills of the Vocational School students in mastering Remote Desktop and TeamViewer technology for solving problems and managing networks remotely. The workshop will provide practical experience that suits the current needs of the IT industry, through direct training and simulations. Considering that the workshop only takes a few hours, the student participants of the workshop can continue their training not only at the school or at home, but also can communicate with the Team of S2 TI UNPAM. If necessary, the follow-up workshops can be carried out either offline or online.